The balance of power in gymnastics at the 2024 Olympics: a comparison between continental associations - Somkin A.A. ,; Smirnova N.N. ,; Agaev R.A. ,; Krotov A.E. , (Theory and Practice of Physical Culture, 2025)
Objective of the study – aims to assess the state of gymnastics in the continental federations that are part of the FIG, based on the results shown at the XXXIII Olympic Games. Methods and structure of the study. As part of the work, the structure of FIG and its five continental unions (CS) were studied. The results of the Olympic gymnastics competitions are analyzed, followed by statistical processing of data on the participation of teams and individual athletes from various CS. The countries and gymnasts who demonstrated the best results at the XXXIII Olympiad have been identified. Results and conclusions. The distribution of medals in gymnastics at the Olympic Games is characterized by significant geographical diversity. Representatives of 17 states from four CS, excluding Oceania, won awards of various merits, including eight countries that won gold medals. Asian countries (Japan, China) occupy the leading positions in men's gymnastics, while American countries (USA and Brazil) occupy the leading positions in women's gymnastics. Individual gymnasts – winners and prize–winners of the Games – represent countries that were not previously among the leaders of world gymnastics, such as the Philippines, Colombia and Kazakhstan for men, as well as Algeria for women. However, for an objective assessment of the balance of power between the CS, it is necessary to take into account the participation of Russia.